An assessment of self-purification of regulated and natural streams - Survilė, Oksana; Šaulys, Valentinas; Stanionytė, Auksė (International Conference “Environmental Engineering”, 2017)
In these latter days it has become topical to reconsider, the technologies and practice of regulated for drainage purposes streams supervision, to find ways how to combine agricultural productivity and restore lost ecological balance at least partially. The article analyzes the influence of natural and regulated stream stretches on water quality and stream self-purification effectiveness. The analysis of nitrate concentration in water samples taken from natural and regulated stream stretches was conducted for the identification of water quality. Nitrate (NO3) concentrations and their alternation during different seasons were studied. The conducted analysis revealed that stream nitrate self-purification is better in natural stream stretches. An average coefficient of self-purification recorded in the course of the research in natural stretches was 0.57, whereas in a regulated stretch – 0.09. On purpose to improve surface-water quality and self-purification effectiveness it is suggested to naturalize regulated stream stretches, to allow woody vegetation grow on slopes, to encourage meandering, pools and shoals forming processes in floodplains.